Analysis of Indonesian Listed Banks’ X-Efficiency, Scale Efficiency, and Profitability Determinants - Cahyana, Nancy (2015)
This study analyzes Indonesian listed banks’ X-efficiency, scale efficiency and profitability determinants using an unbalanced panel of 27 listed banks from 2010 to 2014. It employs the Stochastic Frontier Analysis (SFA) to assess the X-efficiency and scale efficiency through cost function estimation, and the System Generalized Method of Moments (SGMM) is utilized to examine the determinants of bank profitability. The first part of the results show upward trend of X-efficiency for the banking sector with an average of 78.07%. Moreover, it has been found that economies of scale exist, and therefore Indonesian banks exhibit increasing returns to scale. Following Berger’s (1995) model, there is no evidence that X-efficiency and scale efficiency affect profitability of Indonesian listed banks, but the risk factors seem to be prioritized in achieving high profitability of each individual bank.